Developing professional learning in k-based economy and k-society using action learning and action research approaches - Kim, Phaik Lah (Sunway University College, 2004)
Following rapid economic and social advancement, Malaysia has placed a great emphasis on Information and ommunication Technology (ICT) education and training, and particularly on the development of a knowledge or k-based economy and k-society. In the wake of new technologies and k-based activities, there has arisen an enhanced need for learning approaches that will develop professional knowledge and skills in line with new approaches to knowledge creation and utilization. Action Learning (AL) and Action Research (AR) approaches have received recognition as effective strategies for facilitating change in a variety of organizational learning and change-management contexts. This paper examines the basic concepts of AL and AR approaches that are widely used and suggests relevant learning strategies to develop work place or on-the-job learning in a k-based economy and k-society. A few critical success factors in AL and AR approaches are discussed in order to highlight human capacity building for k-workers and k-professionals.